Situation Report: Hungary, 15 June 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian-Romanian Party Talks Fail to Yield Results / by Alfred Reisch Official and Dissident Views on the Magyar Minority in Slovakia / by Edith Markos The Fast-Growing Gypsy Minority and Its Problems / by Edith Markos Inflation and Monetary Policy / by Karoly Okolicsanyi Plans to Introduce Personal Income Tax / by Karoly Okolicsanyi Plans for Value-Added-Tax Passport Restrictions / by Judith Pataki The Institutionalized Perils of Hungarian Hospitals / by Judith Pataki Chinese Premier and Acting Party Secretary to Visit Hungary